Osteoporosis - Cembrowicz, Stefan (Answers at your fingertips., 2007)
The first sign of osteoporosis is usually a broken bone; there are often no prior warning signs. One in two women and one in five men over fifty will experience a fracture. However, early treatment can prevent further serious breaks and ill-health, and it is vital for everyone to be aware of how they can protect themselves against this potentially dangerous and painful condition.